Examination of the vegetative and generative accomplishment of new apple varieties - Csihon, Ádám (Acta Agraria Debreceniensis, 2014)
Our research focuses on apple varieties, what are planted expansively in the development apple orchards of Western-Europe, but about the production characteristics of these varieties we don’t have or just few practical experiences in Hungary. These varieties can be described with regular and high yields, aesthetic and alluring appearance in their origin places, what ensure profitable producing for the growers. In our climate what tends to be often extreme (hard cold winters, late spring frosts, summer drought, heat stress) these varieties may behave differently, so before the substantial planting it is expedient to carry out variety evaluations to avoid the later failures. The place of our experimental is located in the Nyírség, what presents adequately the ecological conditions of the surrounding areas, so the gained results can be easily adapted in the biggest apple production site of Hungary. Regarding the vegetative and the generative parameters of the 14 examined varieties (’Schniga’, ’Jugala’, ’Fendeca’, ’Galaval’, ’Fengal’, ’Red Cap’, ’Early Red One’, ’Jeromine’, ’Crimson Crisp’, ’Red Topaz’, ’Red Jonaprince’, ’Red Idared’, ’Fuji SW’, club variety) we found significant differences, which is the result of the genetically coded characteristics of the varieties, the effects of the vintage, the different training methods and the correlations of these factors.